Titanium dioxide nanotubes: synthesis, structure, properties and applications. (December 2021) - Rempel, Andrey A.; Valeeva, Albina A.; Vokhmintsev, Alexander S.; Weinstein, Ilya A.
Abstract: Methods of synthesis of nanotubular structures based on titania of various phase and chemical compositions are described. A systematic account is given of known data about the influence of synthesis and subsequent treatment conditions on the amorphous and crystal structures, specific surface area, morphology and optical, luminescence and electro-physical properties of titania-based nanotubular oxide materials. The photocatalytic properties in the oxidation reactions of organic compounds and the performance characteristics of the memristive behaviour of TiO2-based nanotubular structures are considered in details. Their applications are discussed. The bibliography includes 238 references.